Effectiveness of Online-Based Peer Counseling Against Academic Anxiety in Class of 2020/2021, Universitas Binawan During the COVID-19 Pandemic - Ratnasartika Apriliyani; Rianda Abdi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The coronavirus disease 2019 (COVID-19) pandemic that has continued since March 2020 requires everyone to develop new habits that have an impact on mental health decline. A new habit that students must face is the transition from face-to-face learning to distance learning, where the learning process uses software applications developed specifically to manage online learning and distribute lecture materials between students and lecturers. This study aims to determine effectiveness of online-based peer counseling against academic anxiety in Class of 2020/2021, Universitas Binawan during the COVID-19 pandemic. This study uses an experimental methodology of one group pre-test and post-test design. The research subjects were 15 respondents who were selected from 847 students who were Universitas Binawan students who had received a recommendation from the Head of the Study Program because their achievement index score was 3.00. The data analysis technique used in this study is t-test using the statistical product and service solution version 17 assistance program. The results showed that online-based peer counseling was effective in reducing academic anxiety in Class of 2020/2021, Universitas Binawan during the COVID-19 pandemic.